Crime, desire and law's unconscious: law, literature and culture - Gurnham, David (Routledge, 2014)
"Sexual desire, and the possible dangers associated with its more extreme manifestations, provokes strong, albeit often contradictory reactions. Such reactions are a well-known stimulant of creative, juridical and scholarly activity, and the texts of law, literature and academic criticism respond to it in ways that are suggestive both of revulsion and fascination. But how are we to understand such responses, and what can they tell us about the relationship between law and its 'others'? Exploring these questions in the context of HIV transmission, on-street sexual exploitation and erotic asphyxiation, this book seeks to understand the motivations behind legal, literary and cultural constructions of sexual offences, their perpetrators and victims. It analyses these constructions in a diverse range of sources: appeal judgments in England & Wales and North America, criminal trials and their reporting, visual and linguistic cultures and both modern and 'classic' literature. The perspective taken here is informed by a psychoanalytic understanding of the uses of metaphor in these texts that may indicate a displacement of troubling unconscious influences, assumptions and prejudices. Sexual behaviours considered to be 'beyond the pale', that we publicly and consciously condemn, may also serve as uncanny reminders of long-forgotten and repressed desires and memories that suggest secret affinities between offenders and the society that judges them"--